Households, Markets and Public Choice - Hans Gersbach; Hans Haller (Center for Economic Studies and ifo Institute (CESifo), 2014)
We develop a model that combines competitive exchange of private commodities across endogenously formed groups with public good provision and global collective decisions. There is a tension between local and global collective decisions. In particular, we show that group formation and collective decisions on public goods may destabilize each other, even if there exist favorable conditions for matching on the one hand, and for global collective decisions on the other hand. We establish sufficient conditions for the existence of competitive equilibria with endogenous household formation and public choice.
Keywords: D10; D51; D62; D70; H20; H41; 330; household formation; matching; general equilibrium; public goods; public choice; median voter theorem